Safety and function of a prototype microprocessor-controlled knee prosthesis for low active transfemoral amputees switching from a mechanic knee prosthesis: a pilot study. (17th February 2018) - Hasenoehrl, Timothy; Schmalz, Thomas; Windhager, Reinhard; Domayer, Stephan; Dana, Sara; Ambrozy, Clemens; Palma, Stefano; Crevenna, Richard
Abstract: Purpose: Aim of this pilot study was to assess safety and functioning of a microprocessor-controlled knee prosthesis (MPK) after a short familiarization time and no structured physical therapy. Materials and methods: Five elderly, low-active transfemoral amputees who were fitted with a standard non-microprocessor controlled knee prosthesis (NMPK) performed a baseline measurement consisting of a 3 D gait analysis, functional tests and questionnaires. The first follow-up consisted of the same test procedure and was performed with the MPK after 4 to 6 weeks of familiarization. After being refitted to their standard NMPK again, the subjects undertook the second follow-up which consisted of solely questionnaires 4 weeks later. Results: Questionnaires and functional tests showed an increase in the perception of safety. Moreover, gait analysis revealed more physiologic knee and hip extension/flexion patterns when using the MPK. Conclusion: Our results showed that although the Genium with Cenior-Leg ruleset-MPK (GCL-MPK) might help to improve several safety-related outcomes as well as gait biomechanics the functional potential of the GCL-MPK may have been limited without specific training and a sufficient acclimation period. Implications for Rehabilitation: Elderly transfemoral amputees are often limited in their activity by safety issues as well as insufficient functioning regarding the non microprocessor-controlled knee prostheses (NMPK), thing that could be eliminated with the use of suitable microprocessor-controlled prostheses (MPK). The safety and functioning of a prototype MPK (GCL-MPK) specifically designed for the needs of older and low-active transfemoral amputees was assessed in this pilot study. The GCL-MPK showed indicators of increased safety and more natural walking patterns in older and low-active transfemoral amputees in comparison to the standard NMPK already after a short acclimatisation time and no structured physical therapy. Regarding functional performance it seems as if providing older and low-active transfemoral amputees with the GCL-MPK alone without prescribing structured prosthesis training might be insufficient to achieve improvements over the standard NMPKs.